Communication Patterns and Their Impact on Social Identity in Wangsa Marriages among Balinese Hindus in Sukapura, North Jakarta - A. Agung Ketut Patera; Tuty Mutiah; Lasmery RM Girsang (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
This study examines the impact of communication patterns on social identity within the Triwangsa marriage system in the Balinese Hindu community. It aims to analyze the formation of communication patterns, the influence of changes in wangsa status on social identity, and the relationship between both aspects. This study is grounded in the concepts of communication patterns, social identity, and cultural symbols, which explain how meaning and social structures are maintained through interaction within the Triwangsa marriage system. A quantitative approach was employed using a survey method. Data were collected through structured questionnaires distributed via Google Forms to 139 respondents from the Paguyuban Agama Hindu at Sukapura Cilincing community in North Jakarta. The data were analyzed using descriptive and inferential statistical techniques. The findings indicate that changes in wangsa status significantly influence communication patterns and contribute to the reconstruction of social identity. This study provides empirical evidence on the transformation of traditional communication patterns within the Triwangsa marriage system and their implications for social identity formation in the Balinese Hindu community.